2016
DOI: 10.1159/000451076
|View full text |Cite
|
Sign up to set email alerts
|

Design of Surfactant Protein B Peptide Mimics Based on the Saposin Fold for Synthetic Lung Surfactants

Abstract: Surfactant protein (SP)-B is a 79-residue polypeptide crucial for the biophysical and physiological function of endogenous lung surfactant. SP-B is a member of the saposin or saposin-like proteins (SAPLIP) family of proteins that share an overall three-dimensional folding pattern based on secondary structures and disulfide connectivity and exhibit a wide diversity of biological functions. Here, we review the synthesis, molecular biophysics and activity of synthetic analogs of saposin proteins designed to mimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 99 publications
(190 reference statements)
1
37
0
Order By: Relevance
“…Human SP-B is a 79 amino-acid, lipid-associating monomer (MW 8.7 kDa) found in the lung as a covalently linked homodimer. Early theoretical studies based on homology comparisons indicated that the SP-B monomer consists of 4-5 α-helices 6 10 with three intramolecular disulfide bridges (i.e., Cys-8 to Cys-77, Cys-11 to Cys-71 and Cys-35 to Cys-46) 11 , and belongs to the saposin protein superfamily 12 . The helical bundle for SP-B folds into two leaves, with one leaf having α-helices 1 (N-terminal helix), 5 (C-terminal helix) and 4 and the other composed of α-helices 2 and 3 13 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human SP-B is a 79 amino-acid, lipid-associating monomer (MW 8.7 kDa) found in the lung as a covalently linked homodimer. Early theoretical studies based on homology comparisons indicated that the SP-B monomer consists of 4-5 α-helices 6 10 with three intramolecular disulfide bridges (i.e., Cys-8 to Cys-77, Cys-11 to Cys-71 and Cys-35 to Cys-46) 11 , and belongs to the saposin protein superfamily 12 . The helical bundle for SP-B folds into two leaves, with one leaf having α-helices 1 (N-terminal helix), 5 (C-terminal helix) and 4 and the other composed of α-helices 2 and 3 13 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Existing clinically available formulations are extracted from lung lavages or homogenates from pigs (Curosurf®) and cows (Infasurf®, Survanta®), and contain small amounts of SP-B and SP-C (<< 2% of total weight) in a lipid extract with DPPC as its main component. Based on the predicted 3D-saposin motif for SP-B, we have developed minimal SP-B constructs that have desirable structural properties and maintain high activities in animal models of surfactant deficiencies 9 10 . For example, Super Mini-B (SMB) is a 41-residue, ‘short-cut’ peptide ( Figure 1A ), based on the primary sequence, secondary structure and tertiary folding of the known sequence of native SP-B (79-residues), that mimics the high surfactant activity of its parent protein 10 14 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cys-8 to Cys-77, Cys-11 to Cys-71 and Cys-35 to Cys-46). The helical bundle for SP-B is folded into two leaves and held together with disulfide bridges, with one leaf having α-helices 1 (N-terminal helix), 5 (C-terminal helix) and 4 and the second composed of α-helices 2 and 3 [4,5]. Using truncated synthetic peptides (e.g.…”
mentioning
confidence: 99%
“…Cys-8 to Cys-77 and Cys-11 to Cys-71) to form an αhelix hairpin. Mini-B shows high surface activity in vitro and in animal models of surfactant deficiencies, which may be due to this mimic accurately reproducing the topology of the N-and C-terminal domains in the native SP-B [5]. Adding the hydrophobic N-terminal insertion sequence of SP-B (i.e.…”
mentioning
confidence: 99%